Neonatal Outcome In Severe Malaria with Pregnancy - Fazari, Atif Bashir (مجلة الجزيرة للعلوم الصحية; مجلد 1 عدد 1 (2004), 2004)
Pregnant women are more vulnerable to malaria, because of changes in the immune system during pregnancy. It is known that malaria infection during pregnancy, induce a potentially harmful response, in the placenta and the fetus. This study designed to determine the outcome of the neonates in cases of severe malaria. Twenty- five cases observed during acute malarial attack proved by positive parasite in peripheral blood film with severe parasitaemia in different time in their third trimester. This observation depends on different parameters studied here. Seven stillborn (28%).  Ten low birth weight (40%). Four with low Apgar score (16%).  Six born prematurely (24%), two of them, ended in early neonatal death. Further multi central studies with advanced measures recommended studying fetal response during acute attack of malaria.